Intelligent home - Mayeesha, Nazmun Tabassum; Jalal, S.A.M. Martuza; Shams, Fayequa (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.